Pengaruh Penerapan CRM dalam Meningkatkan Kepuasan Warga Kelurahan Wonorejo Rungkut - Brigita Febi Valensiana; Sulastri Irbayuni (BADAN PENERBIT STIEPARI PRESS, 2023)
CRM (Customer Relationship Management) is a strategy for a company or organization that aims to manage interactions with customers. The benefit of implementing CRM is to maintain reciprocal relationships with customers so that they can increase benefits for the company and increase customer satisfaction itself. In the context of public services and population administration, residents are considered as customers. One agency that implements CRM in its service process is the Wonorejo Rungkut sub-district. CRM helps manage the relationship between the Wonorejo Rungkut sub-district and residents so that it can improve service quality and citizen satisfaction in terms of population administration. The forms of CRM carried out by the Wonorejo Rungkut sub-district are by conducting services at RW halls, utilizing the use of social media, putting up leaflets, and conducting outreach. The method used in this journal is a qualitative and quantitative approach. The research results were obtained from the distribution of questionnaires and the author's observation of the events that occurred. The conclusion of this journal is that the CRM method implemented by the Wonorejo Rungkut sub-district has an impact on increasing the satisfaction felt by residents when managing population administration. Keywords: CRM, population administration services, residents satisfaction